Pengaruh Kombinasi Aromaterapi Mawar dan Hipnoterapi terhadap Kecemasan Ibu Hamil saat Pemeriksaan Triple Eliminasi di UPTD Puskesmas Kuta II - Shasi Phaskani (JURNAL MEDIKA USADA, 2023)
Introduction: Pregnancy is a physiological process that almost every woman goes through. Pregnant women must have their pregnancies checked on a regular basis and receive integrated antenatal care. A laboratory examination, one of them is a triple elimination examination, as one of the minimum integrated antenatal service standards. Blood is drawn during the examination, which often causes anxiety in patients. Rose aromatherapy and hypnotherapy are non-pharmacological methods that can help patients relax and reduce anxiety. This study aimed at determining the effect of combining between rose aromatherapy and hypnotherapy on anxiety of pregnant women during triple elimination examination. Methods: This study was carried out at the UPTD. Kuta II Public Health Centre in November - December 2022, employing a pre-experimental research design with a one-group pretest-posttest design. Non-probability sampling was used, along with accidental sampling. The STAI (State Trait Anxiety Inventory) sheet was used to assess anxiety, and the Wilcoxon Sign Rank Test was used to analyze the data. Result: According to the study’s findings of 28 pregnant women, the average anxiety level before the intervention was 54.04, while the average anxiety level after the intervention was 26.50. Anxiety level analysis with Wilcoxon yielded a p-value (p-value = 0.000, α = 0.05), so H0 was rejected and Ha was accepted, indicating that there was an effect of combining between rose aromatherapy and hypnotherapy on anxiety of pregnant women during triple elimination examination at UPTD. Kuta II Public Health Centre. Suggestion: According to the findings of this study, the administration of a combination between rose aromatherapy and hypnotherapy can be used as a consideration in providing midwifery care to pregnant women, particularly those who will undergo blood tests. Keywords: aromatherapy, hypnotherapy, pregnant women, anxiety